Effect of post-cessation hyperglycemia on cardiovascular disease and mortality among middle-aged men: an eight-year longitudinal study. Issue 1 (December 2017) - Choi, Seulggie; Kim, Kyuwoong; Chang, Jooyoung; Kim, Sung; Koo, Hye-Yeon; Jun, Ji-Hye; Cho, Mi; Lee, Kiheon; Park, Sang
Abstract Smoking cessation reduces the risk of cardiovascular disease (CVD), but also elevates fasting serum glucose (FSG) levels. The effect of post-cessation hyperglycemia on cardiovascular disease is unknown. The study population consisted of 127, 066 men without type 2 diabetes from the Korean National Health Insurance System – Health Screening Cohort database. Change in smoking habits and FSG was determined by the difference in smoking status and FSG levels from the first (2002 and 2003) and second (2004 and 2005) health examinations. Continual smokers, quitters, ex-smokers, and never smokers were stratified according to FSG elevation. The study participants were followed-up for CVD and CVD-related death from 2006 to 2013. Compared to continual smokers, quitters had decreased risk of CVD among those without FSG elevation (hazard ratio, HR, 0.76, 95% confidence interval, CI, 0.66–0.86) and with FSG elevation (HR 0.83, 95% CI 0.72–0.96). Similarly, quitters had a tendency towards reduced risk of CVD-related death among those without FSG elevation (HR 0.74, 95% CI 0.51–1.09) and with FSG elevation (HR 0.68, 95% CI 0.46–1.03). Post-cessation hyperglycemia did not attenuate the beneficiary risk-reducing effects of quitting on CVD and CVD-related death.